2020
DOI: 10.1177/1535370220903463
|View full text |Cite
|
Sign up to set email alerts
|

Rutin promotes osteogenic differentiation of periodontal ligament stem cells through the GPR30-mediated PI3K/AKT/mTOR signaling pathway

Abstract: Rutin is one of the flavonoids found in fruits and vegetables. Recent reports have revealed that rutin is a major player in proliferation and bone development. However, data on how rutin regulates the proliferation of periodontal ligament stem cells (PDLSCs), as well as the differentiation of osteogenic cells are scanty. Here, our findings showed that rutin enhanced PDLSCs proliferation, increased ALP activity, and matrix mineralization. Moreover, rutin significantly promoted the expression of osteogenic genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 47 publications
0
30
0
Order By: Relevance
“…In this study, we further showed it is also expressed in rat and mice osteogenic cells. GPER-1 has been suggested to play a role in bone development [7,12,27], and mediate the effect of chemicals, such as rutin and ligustilide, on osteogenic differentiation [28,29]. A study showed that GPER-1 activation promotes osteogenesis on the pre-osteoblast cells, MC3T3E1, through the AMPK/anti-acetyl-CoA carboxylase (ACC) pathway [30].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we further showed it is also expressed in rat and mice osteogenic cells. GPER-1 has been suggested to play a role in bone development [7,12,27], and mediate the effect of chemicals, such as rutin and ligustilide, on osteogenic differentiation [28,29]. A study showed that GPER-1 activation promotes osteogenesis on the pre-osteoblast cells, MC3T3E1, through the AMPK/anti-acetyl-CoA carboxylase (ACC) pathway [30].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in cells treated with a high concentration of compound 7 , the expression level of MyoD was not different compared to that of the non-treated cells. Flavonoids and plant extracts containing flavonoid derivatives have been reported to activate osteogenic and myogenic differentiation as well as glucose resistance regulation via PI3K/Akt/mTOR pathways [ 25 , 26 , 27 , 28 ]. Meanwhile, amino acids are important regulators of the activation of mTOR complex 1, which regulates essential cellular processes such as growth, proliferation, and survival [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…GPR30 is a common target for isoflavones to promote a rapid cellular signaling (Khan et al, 2015;Liu et al, 2018), and it is expressed in the central nervous system, skin, adipose tissue, and skeletal muscle, as well as in monocytes, eosinophils, and neutrophils (Rettew et al, 2010;Notas et al, 2020). Furthermore, GPR30 expression was also observed in cartilage and bone during an inflammatory response (Kang et al, 2015;Ribeiro et al, 2020;Zhao et al, 2020). Activation of GPR30 results in increased intracellular levels of cyclic adenosine monophosphate (cAMP) and activates the PKA signaling pathway, the best known cAMP effector (Mizukami, 2010;Liu et al, 2018) and an essential pathway for a successful inflammation resolution (Lima et al, 2017;Tavares et al, 2020).…”
Section: Introductionmentioning
confidence: 99%